How Untidiness Moves the Motor System. Issue 3 (June 2022) - Fiori, Francesca; Ciricugno, Andrea; Rusconi, Maria Luisa; Slaby, Ryan J.; Cattaneo, Zaira
Humans tend to prefer order to disorder. Orderly environments may provide individuals with comfort due to predictability, allowing a more efficient interaction with objects. Accordingly, a disorderly environment may elicit a tendency to restore order. This order restoration tendency may be observed physiologically as modulation within corticospinal excitability; the latter has been previously associated with motor preparation. To test these hypothesized physiological indices of order restoration, we measured possible changes in corticospinal excitability, as reflected by the amplitude of motor-evoked potentials (MEPs) elicited by single-pulse transcranial magnetic stimulation (TMS) over the primary motor cortex while participants viewed ordered and disordered rooms. We found that images depicting disorderly environments suppressed excitability within the corticospinal tract, in line with prior findings that motor preparation is typically associated with decreased corticospinal excitability. Interestingly, this pattern was particularly evident in individuals that displayed subclinical levels of obsessive-compulsive traits. Thus, a disorderly environment may move the motor system to restore a disorderly environment into a more orderly and predictable environment, and preparation for "order" may be observed on a sensorimotor basis.